Kajian Evaluasi Pasca Huni Desain Interior Ruang Kelas Program Studi Desain Interior Universitas “X” Surabaya - Devina Laudi (Intra, 2017)
In this more advancing era, society has become more aware of the importance of knowledge.This is evident in the increasing number of people registered at institutions providing education. One of the educational institutions is "X" University in Surabaya which participates in fulfilling the society's needs of knowledge. This research was conducted to find out and elaborate the evaluation results on post-occupied classrooms towards the room formation elements (floors, ceilings, walls), the room conditioning elements (lighting, atmosphere, acoustic systems, circulations, and interior designs), and the room filling elements (furniture) as well as the comfort of the classroom occupants of the Interior Design major in "X" University in Surabaya. The methods used for this research is Post Occupancy Evaluation (POE) and qualitative-quantitative methodology to obtain any available information from the 11 classes that have been observed individually to come to solid evidence. The research results show that every class has more or less similar problems related to the room formation elements (floors, ceilings, walls), the room conditioning elements (lighting, atmosphere, acoustic systems, circulations, and interior designs), and the room filling elements (furniture), so some alternative solutions have been formulated regarding the material choices for the classrooms.